2010
DOI: 10.1111/j.1365-2753.2010.01423.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients Assessment of Chronic Illness Care (PACIC) in two Australian studies: structure and utility

Abstract: The two-factor structure of the PACIC found in these Australian studies is different from the five-factor structure found in the US and the European studies. This may be related to differences in the way patients interact with the health system especially the use of Team Care plans. The association of total scores with patient characteristics was consistent with those found in other studies including a lack of association with gender, age and ethnicity. These findings should be taken into consideration when co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
5
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 13 publications
5
46
5
1
Order By: Relevance
“…As in our study, an alternative approach consisted in using an exploratory factor analysis (EFA) to emerge the number of dimensions from the data. In the literature this approach has been used in 5 studies, with 2 studies identifying 5 dimensions [25,41] and the 3 others studies identifying 1 or 2 dimensions [28,42]. Our 2-dimension structure of the PACIC is more closely related to these last validation studies which included items in more general dimensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in our study, an alternative approach consisted in using an exploratory factor analysis (EFA) to emerge the number of dimensions from the data. In the literature this approach has been used in 5 studies, with 2 studies identifying 5 dimensions [25,41] and the 3 others studies identifying 1 or 2 dimensions [28,42]. Our 2-dimension structure of the PACIC is more closely related to these last validation studies which included items in more general dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…These results are partly in line with the literature. In terms of self-reported health, 2 studies have previously investigated the relationship with the PACIC score(s) and concluded to significance [37,42]. In terms of age, the evidence is mixed: in the 9 studies which tested the relationship with PACIC score, only 3 showed a significant result [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…We chose to use the PACIC instrument among others because an Australian study concluded that it was a feasible instrument for comparing patients’ assessment of the quality of care in those situations where they interact with the healthcare system, especially where emphasis is given to self-management [45]. Furthermore, Vrijhoef concluded that the PACIC instrument is the most appropriate instrument among the existing generic instruments that measure patients’ experience of their integrated care for chronic conditions [46].…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with existing literature The mean PACIC total was 2.4, compared with means of 2.6 in patients in US primary care, 26 3.3 in primary care patients with depression in Germany, 38 2.7 in patients with osteoarthritis in German primary care, 39 3.0 in patients with CHD, hypertension, or diabetes in Australian general practice, 40 and 3.2 in Hispanic patients with diabetes in hospital ambulatory settings in the US. 41 Although there may be other variables that confound these comparisons, they do suggest that patients in the cohort perceived that they were experiencing low levels of care planning, despite high levels of overall satisfaction (Table 1).…”
Section: -17mentioning
confidence: 91%